The significance of Exo1 K589E polymorphism on cancer susceptibility: evidence based on a meta-analysis. - Fujiao Duan (Public Library of Science (PLoS), 2014)
The exonuclease1 (Exo1) gene is a key component of mismatch repair (MMR) by resecting the damaged strand, which is the only exonuclease involved in the human MMR system. The gene product is a member of the RAD2 nuclease family and functions in DNA replication, repair and recombination. However, whether Exo1 is required to activate MMR-dependent DNA damage response (DDR) remains unknown, the conclusions of the Exo1 polymorphisms on cancer susceptibility studies were not consistent. We carried out a meta-analysis of 7 case-control studies to clarify the association between the Exo1 K589E polymorphism and cancer risk. Overall,a significant association of the Exo1 K589E polymorphism with cancer risk in all genetic models (Lys vs Glu: OR = 1.51, 95%CI:1.39-1.99, P<0.01; Glu/Lys vs Glu/Glu: OR = 1.43, 95%CI:1.28-1.60, P<0.01; Lys/Lys vs Glu/Glu: OR = 2.45, 95%CI:1.90-3.17, P<0.01; Lys/Lys+Glu/Lys vs Glu/Glu: OR = 1.53, 95%CI:1.38-1.71, P<0.01; Glu/Glu vs Glu/Lys+Lys/Lys: OR =  2.27, 95%CI:1.79-2.89, P<0.01). In the stratified analysis by ethnicity, significantly increased risk was observed in Asian population (Lys vs Glu: OR = 1.53, 95%CI:1.39-1.69, P<0.01; Glu/Lys vs Glu/Glu: OR = 1.50, 95%CI:1.34-1.69, P<0.01; Lys/Lys vs Glu/Glu: OR = 2.48, 95%CI:1.84-3.34, P<0.01; Lys/Lys+Glu/Lys vs Glu/Glu: OR = 1.58, 95%CI:1.41-1.78, P<0.01; Glu/Glu vs Glu/Lys+Lys/Lys: OR = 2.18, 95%CI:1.62-2.93, P<0.01). Subgroup analysis based on smoking suggested Exo1 K589E polymorphism conferred significant risk among smokers (Lys/Lys+Glu/Lys vs Glu/Glu: OR = 2.16, 95%CI:1.77-2.63, P<0.01), but not in non-smokers (Lys/Lys+Glu/Lys vs Glu/Glu: OR = 0.89, 95%CI:0.64-1.24, P = 0.50). In conclusion, Exo1 K589E Lys allele may be used as a novel biomarker for cancer susceptibility, particularly in smokers.